Youthful socialities in Australia's urban multiculture. (February 2018) - Harris, Anita
This article considers the function of friendship as a form of urban relation for young people living in working class areas of Australia's multicultural capital cities. These neighbourhoods are characterised by very high diversity, significant socioeconomic disadvantage and large youth populations, and over the last five years many have received the largest influx of refugees and migrants of any Australian municipality. Against this backdrop, this article investigates the ways that sociality is produced amongst young people of many backgrounds who must constantly negotiate interethnic propinquity in their daily lives. It explores how young people create ways of being together beyond and beneath the imperatives of formal social cohesion initiatives to participate in harmonious community-making. It argues that everyday forms of convivial co-habitation are produced and regulated through friendship relations and networks that embed mix in daily life, and these can serve to recognise and manage, rather than eliminate, intensity, conflict and ambivalence. It suggests that such practices of sociality complicate mainstream policy endeavours, and can offer some important and hopeful ways to expand theorisation of social relations in the multicultural city.